2012
DOI: 10.1182/blood-2012-03-417022
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α is a negative regulator of plasmacytoid DC development in vitro and in vivo

Abstract: IntroductionMammalian hematopoiesis in the BM is regulated among others by the oxygen (O 2 ) availability. O 2 concentrations in the BM range from anoxia to 6% opposed to 4%-14% in well-oxygenated tissues, including the blood. 1,2 Recent data indicate that O 2 gradients within the BM participate in keeping hematopoietic stem cells (HSCs) in a low-replicating pluripotent state. HSCs are located in an extremely hypoxic niche as demonstrated by dye-perfusion and engraftment studies. 3,4 Hypoxia-inducible factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Nevertheless, this transcription factor impairs the upregulation of CCR7, a chemokine involved in homing of mature DCs to secondary lymphoid organs [ 53 , 85 ]. Moreover, HIF-1α acts as a negative regulator of plasmacytoid dendritic cell development [ 86 ]. Our results reveal a detrimental role for HIF-1α in DC function during experimental VL.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this transcription factor impairs the upregulation of CCR7, a chemokine involved in homing of mature DCs to secondary lymphoid organs [ 53 , 85 ]. Moreover, HIF-1α acts as a negative regulator of plasmacytoid dendritic cell development [ 86 ]. Our results reveal a detrimental role for HIF-1α in DC function during experimental VL.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factors influence hematopoiesis and maintain HSC function. Recently, it was shown that low oxygen content upregulates ID2 and suppresses FLT3L-induced pDC development, in a manner dependent on HIF1α 227 . GFI1 controls the development and functions of pDCs and cDCs in a STAT3-dependent manner 228 and represses Rag transcription in pDCs 229 .…”
Section: Development Of Pdcsmentioning
confidence: 99%
“…BMDM from C57BL/6 WT mice and various knock out and transgene mice were generated in Teflon® bags, as described earlier [80]. In addition to C57BL/6 WT mice (Charles River Breeding Laboratories, Sulzfeld, Germany), we used GFP-MAP1LC3 mice [81], cybb -/mice [82] and their littermate controls, atg7 cKO (Atg7 F/F : Lyz2-Cre) mice [83,84] and their littermate controls, and hif1a cKO (Hif1a F/F : Lyz2-Cre) mice [85] and their respective littermate controls as described earlier [86,87]. For infection experiments, we used E. coli HB101 or, for immunofluorescence studies, E. coli harboring pWRG167 [88] and pWRG29 for constitutive expression of superfolder GFP (sfGFP) or super cyan fluorescent protein 3A (sCFP3A), respectively.…”
Section: Cells and Bacteriamentioning
confidence: 99%